Enhanced decomposition and nitrogen mineralization sustain rapid growth of Eucalyptus regnans after wildfire. (6th October 2016) - Dijkstra, Feike A.; Jenkins, Meaghan; de Rémy de Courcelles, Vivien; Keitel, Claudia; Barbour, Margaret M.; Kayler, Zachary E.; Adams, Mark A.
Summary: Eucalyptus regnans grows rapidly from seed after wildfires, out‐competing other species, thereby forming pure stands of mature forests that rank amongst the world's most carbon dense. By global standards, these forests grow on infertile soils. It is unclear how E. regnans is able to obtain large amounts nitrogen (N) from these infertile soils to support its rapid growth after fire. We measured carbon (C) and N stored in plant biomass and photosynthetic rates of E. regnans 2 years after a wildfire and examined whether E. regnans stimulated its own N supply through root‐induced increases in microbial decomposition and N mineralization. We compared microbial biomass, gross N mineralization rates and soil C in trenched and rooted plots. Photosynthetic rates of E. regnans seedlings were high and comparable to photosynthetic rates observed in fertilized crops. Presence of roots of E. regnans and allied microflora enhanced gross N mineralization more than fivefold compared to soil without roots present. Soil microbial biomass was more than doubled by root presence. The soil N pulse caused by the fire and N mineralization rates in the absence of roots were too small to account for the large amount of N stored in E. regnans 2 years after the fire. Our results suggest that E. regnans facilitated its rapid growth by enhancing microbial activity and N mineralization. This enhanced microbial activity also contributed to a substantial loss of soil C (˜62% of carbon gained in plant biomass was concurrently lost from soil). Synthesis . At the ecosystem scale, the synergistic effects of plant growth and soil N mineralization need to be carefully assessed against costs to soil C for forests regenerating after disturbance. Abstract : We found that mountain ash ( Eucalyptus regnans ) strongly enhanced microbial decomposition and nitrogen mineralization to facilitate its growth after a wildfire. At the ecosystem scale, the synergistic effects of plant growth and soil N mineralization need to be carefully assessed against costs to soil C for forests regenerating after disturbance.